«Zhazmysh» is needed new look. (Eurasian Journal of Philology Science and Education, 2015)
In article it is spoken about art feature, about literary skill, about continuity with works of such genre, about a way of expression of reality of life, about a method of the author used in the statement of the opinion in the memorial essay of the prominent representative of the Kazakh literature, the national writer of Kazakhstan, the translator, poetKadyr Myrza Ali "Zhazmysh". And about that in this work is put and considered moral, philosophical, political, esthetic affairs; the image and type of the person becomes clear not only from the point of view of the importance of the people, but also from the point of view of world culture, the human being; and that the personal opinion of thewriter influences an explanation and frankness of character of the modern person; and that the writer concludes the works by such concepts as honor, glory and that the author raises questions which are considered as the eternal.And about that the importance and originality of the brought-up questions in an instruction essay "Zhazmysh" are given by a suitable literary method, it characterizes skill of the writer.
Keywords: booklet-essay; «Zhazmysh»; poet; writer; creative personality; fate of writer